Postnatal environment affects auditory development and sensorimotor gating in a rat model for autism spectrum disorder - Doornaert, Ella Elizabeth; Mohamad, Alaa El-Cheikh; Johal, Gurwinder; Allman, Brian Leonard; Möhrle, Dorit; Schmid, Susanne (Frontiers in Neuroscience, 2025)
The homozygous Cntnap2 knockout (KO) rat is a well-established genetic model for neurodevelopmental disorders, exhibiting core features of autism spectrum disorder (ASD), including impaired sensory processing and sensorimotor gating. Recent findings indicate that the severity of ASD-like phenotypes in Cntnap2 KO offspring is influenced by the parental genotype, with more pronounced impairments observed in KO rats bred from homozygous pairs compared to heterozygous pairs (Cntnap2 HET). However, it is unclear to what extent this is due to in utero versus postnatal effects. We, therefore, investigated how early postnatal environmental factors, shaped by differences in parental and littermate genotypes, influence auditory processing and sensorimotor gating in Cntnap2 KO rats. To examine this, we cross-fostered Cntnap2 KO pups bred from Cntnap2 KO rats to be reared with litters of Cntnap2 HET dams. Cross-fostering Cntnap2 KO rats reversed or partially reversed delayed hearing sensitivity maturation, heightened acoustic startle responses, and deficits in prepulse inhibition of the acoustic startle response. However, cross-fostering also exacerbated deficits in the neural responsiveness and conductivity in the auditory brainstem, as well as in gap-induced prepulse inhibition of the acoustic startle response. These results emphasize the importance of considering the postnatal environment and breeding strategies in preclinical genetic models of neuropsychiatric disorders. More importantly, they also demonstrate that ASD-like traits, including alterations in brainstem sensory processing, are not strictly determined by genetic factors, but remain malleable by environmental factors during early postnatal development.